PEMANFAATAN DISCORD SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN SECARA DARING - Muhammad Badrul Huda - Universitas Bhinneka PGRI (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
The COVID-19 pandemic that has hit almost all countries in the world, including Indonesia, has had an impact on various sectors, one of which is the education sector. The impact is the implementation of the distance learning process which indirectly encourages the development of the use of technology in the world of education itself, especially by educational institutions. Various learning media were then developed or used as an effort to support this, one of which is Discord. The use of Discord itself has been developed by several educational communities such as Neo Historia and Ruang Belajar. This study aims to explore ways of using Discord by the two communities to be able to describe the technique of using the application as an interesting learning medium. Through a qualitative approach method that aims to describe the results of research in more depth obtained through literature study and observation. The results of this study indicate that the maximum use of various features available in Discord such as text and voice channels, channel distribution, role systems, and bots. and the combination with other media can be a factor causing Discord to become an interesting and interactive learning media.Keywords: learning media, discord